2020
DOI: 10.1002/smll.202000690
|View full text |Cite
|
Sign up to set email alerts
|

The Known and Unknown about the Environmental Safety of Nanomaterials in Commerce

Abstract: The widespread nanomaterial use in commercial products has fed significant concern over environmental health and safety ramifications. Initially, little was known as to how these highly reactive particulates interacted with biological systems. Nanomaterials have introduced complexities not normally considered in traditional safety assessments of chemicals and therefore have generated uncertainty in the reliability of standard tests of safety. Advances in understanding the potential impacts of nanomaterials hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 98 publications
1
9
0
Order By: Relevance
“…In the past two decades, substantial work has been carried out toward understanding the potential implications of the increasing commercial use of engineered nanomaterials (ENMs) on human health and the environment, with more than 18,000 nanotoxicology articles published between the years 2000 and 2018. Over this period, studies of ENM impacts grew from basic toxicity exposures to increasingly sophisticated studies aimed at understanding how the ENM properties determine toxicity, mechanisms by which materials interact with biological systems, and how and what materials and their environmental transformations may be of potential concern. , To date, nanotoxicology has focused largely on first-generation ENMs (e.g., Au, Ag, and graphene). ,, When an underlying mechanism is proposed, toxicity is frequently attributed to reactive oxygen species (ROS) for a diversity of ENMs including Au, Ag, CeO, Si, and carbon nanotubes. ROS such as superoxides, hydrogen peroxides, and hydroxyl radicals have long been classified as damaging to DNA, RNA, proteins, and lipids . However, research within the last decade has revealed ROSspecifically superoxide and its hydrogen peroxide product generated in the mitochondria or by NADPH oxidasesas important signaling molecules , involved in regulating the fundamental biological processes through oxidation of cysteines of protein redox sensors including metabolism (e.g., GAPDH, PKM2, and AMPK), proliferation (e.g., PTEN, PTP1b, and EGFR), autophagy (e.g., PTEN, AMPK, Atg4, and FOXO), and apoptosis (e.g., VDAC, caspases, ERO1, and PDI); and ROS are actively generated during and required for normal embryonic development across species .…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, substantial work has been carried out toward understanding the potential implications of the increasing commercial use of engineered nanomaterials (ENMs) on human health and the environment, with more than 18,000 nanotoxicology articles published between the years 2000 and 2018. Over this period, studies of ENM impacts grew from basic toxicity exposures to increasingly sophisticated studies aimed at understanding how the ENM properties determine toxicity, mechanisms by which materials interact with biological systems, and how and what materials and their environmental transformations may be of potential concern. , To date, nanotoxicology has focused largely on first-generation ENMs (e.g., Au, Ag, and graphene). ,, When an underlying mechanism is proposed, toxicity is frequently attributed to reactive oxygen species (ROS) for a diversity of ENMs including Au, Ag, CeO, Si, and carbon nanotubes. ROS such as superoxides, hydrogen peroxides, and hydroxyl radicals have long been classified as damaging to DNA, RNA, proteins, and lipids . However, research within the last decade has revealed ROSspecifically superoxide and its hydrogen peroxide product generated in the mitochondria or by NADPH oxidasesas important signaling molecules , involved in regulating the fundamental biological processes through oxidation of cysteines of protein redox sensors including metabolism (e.g., GAPDH, PKM2, and AMPK), proliferation (e.g., PTEN, PTP1b, and EGFR), autophagy (e.g., PTEN, AMPK, Atg4, and FOXO), and apoptosis (e.g., VDAC, caspases, ERO1, and PDI); and ROS are actively generated during and required for normal embryonic development across species .…”
Section: Introductionmentioning
confidence: 99%
“…Of course, for a practical use on nanoantioxidants, this list must be integrated with toxicological and environmental considerations [119], that go beyond the aims of this review [120]. Nevertheless, we believe that the use of these guidelines will inspire the research of novel nanomaterials able to cope with the autoxidation of organic materials in fields spanning from foods to plastic to biological systems.…”
Section: Discussionmentioning
confidence: 99%
“…The sheer number and diversity of ENM-containing products, systems, and devices have brought nanotechnology applications into everyday use by millions of consumers, making it difficult to gain detailed awareness of nanotechnology in the marketplace. 41 Understanding the commercial presence of ENMs will enable a more complete assessment of where exposures may occur and is fundamental to life-cycle assessments. Developing decision support tools and methods that regulatory agencies can use for risk assessment of nanomaterials in food and environmental media and then funding research to develop data as needed would represent a novel approach.…”
Section: Critical Issues and Opportunities Going Forwardmentioning
confidence: 99%